Gastric cancer surgery in cirrhotic patients: Result of gastrectomy with D2 lymph node dissection - Lee, Jun Ho (World J Gastroenterol, 2005)
AIM: To explore the feasibility of performing gastrectomy with D2 lymphadenectomy in gastric cancer patients with liver cirrhosis. METHODS: A total of 7 178 patients were admitted with a diagnosis of liver cirrhosis from January 1993 to December 2003. We reviewed the records of 142 patients who were diagnosed with liver cirrhosis and gastric adenocarcinoma during the same period. Gastrectomy with D2 lymph node dissection for carcinoma of the stomach was performed in 94 patients with histologically proven hepatic cirrhosis. RESULTS: All but 12 patients were classified as Child’s class A. Only 35 patients (37.2%) were diagnosed with cirrhosis before operation. Seventy-three patients underwent a subtotal gastrectomy (77.7%) and 21 patients (22.3%) underwent a total gastrectomy, each with D2 or more lymph node dissection. Two patients (3.8%) who had prophylactic intra-operative drain placement, died of postoperative complications from hepatorenal failure with intractable ascites. Thirty-seven patients (39.4%) experienced postoperative complications. The extent of gastric resection did not influence the morbidity whereas serum aspartate aminotransferase level (P = 0.011) and transfusion did (P = 0.008). The most common postoperative complication was ascites (13.9%) followed by wound infection (10.6%). CONCLUSION: We concluded that the presence of compensated cirrhosis, i.e. Child class A, is not a contraindication against gastrectomy with D2 or more lymph node dissection, when curative resection for gastric cancer is possible. Hepatic reserve and meticulous hemostasis are the likely determinants of operative prognosis.